2014
DOI: 10.1021/ml500161v
|View full text |Cite
|
Sign up to set email alerts
|

Two Potent OXE-R Antagonists: Assignment of Stereochemistry

Abstract: 5-Oxo-6,8,11,14-eicosatetraenoic acid (5-oxo-ETE) is formed by the oxidation of 5-hydroxy-6E,8Z,11Z,14Z-eicosatetraenoic acid (5-HETE), which is a major metabolite of enzymatic oxidation of arachidonic acid (AA). 5-Oxo-ETE is the most potent lipid chemoattractant for human eosinophils. Its actions are mediated by the selective OXE receptor, which is therefore an attractive target in eosinophilic diseases such as allergic rhinitis and asthma. Recently, we have reported two excellent OXE receptor antagonists tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For further studies on the pharmacokinetics and metabolism of 230 we focused on the active S-enantiomer ( S230 ), which is over 400 times more potent than the R-enantiomer ( R230 ) [8, 9]. To provide the gram-amounts of antagonist that would be required for this and subsequent in vivo studies we developed a novel procedure using the chiral reagent (S)-Tol-BINAP for the synthesis of the chiral acyl side chain of S230 [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For further studies on the pharmacokinetics and metabolism of 230 we focused on the active S-enantiomer ( S230 ), which is over 400 times more potent than the R-enantiomer ( R230 ) [8, 9]. To provide the gram-amounts of antagonist that would be required for this and subsequent in vivo studies we developed a novel procedure using the chiral reagent (S)-Tol-BINAP for the synthesis of the chiral acyl side chain of S230 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Modification of this compound led to the identification of the chiral compound 230 (Fig. 1) as a potent and selective OXE receptor antagonist [8], with the antagonist activity residing almost exclusively in the S-enantiomer ( S230 ) [9]. …”
Section: Introductionmentioning
confidence: 99%
“…This compound is a racemic mixture of two enantiomers, separation of which by chiral-HPLC revealed that the biological activity resides almost exclusively in a single enantiomer. We were able to synthesize both enantiomers by chiral synthesis [175] and found the S-enantiomer (i.e. S-264 ) was the one with potent antagonist activity (Fig.…”
Section: Biological Actions Of Hetes and Oxoetesmentioning
confidence: 99%
“…Although it possesses only weak biological activity itself, 5-HETE can be oxidized to 5-oxo-6,8,11,14-eicosatetraenoic acid (5-oxo-ETE), which is a potent chemoattractant for eosinophils and neutrophils [22] and a major metabolite of enzymatic oxidation of AA. 5-oxo-ETE may be an important mediator in asthma, and an attractive target in eosinophilic diseases, such as AR and asthma [23,24]. Several lines of evidence indicate that respiratory infection and cell injury may activate the 12/15-LOX pathway in airway epithelial cells, and markedly increase their production of AA, 12-S-HETE and 15-HETE, which play a pathophysiological role in asthma [25,26].…”
Section: Introductionmentioning
confidence: 99%